Pengaruh Modal Kerja Terhadap Profitabilitas Pada PT.HM Sampoerna Yang Terdafatar Di Bursa Efek Indonesia Tahun 2019 – 2023 - Florida Tresia Weking; Andreas Rengga; Kristiana Reinaldis Aek (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The issue addressed in this research is the fluctuating working capital at PT: HM Sampoerna, a cigarette company listed on the Indonesia Stock Exchange between 2019 and 2023. The study aimed to examine the influence of working capital on profitability. The population of this research comprised cigarette companies, specifically PT.HM Sampoerna that listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling, resulting in a single company being analyzed. Data were collected through documentation and analyzed using descriptive and inferential statistics, specifically simple linear regression. Hypothesis testing was conducted using a t-test. The descriptive analysis revealed that: (1) The average (mean) working capital amounted to IDR. 21,251,620,600. (2) The net profit margin had an average value of IDR 18.8, indicating that the company generated IDR for every IDR. 1 in sales. IDR 18.8 in gross profit. The t-test results showed that working capital (X) positively and significantly influenced the net profit margin (Y). The determination analysis (R³) indicated that working capital explained 96.9% of the variation in the profitability of PT. HM Sampoerna, as listed on the Indonesia Stock Exchange